Modelling the Effect of the Super‐X Divertor in MAST Upgrade on Transition to Detachment and Distribution of Volumetric Power Losses. Issue 4 (June 2014) - Havlíčková, E.; Wischmeier, M.; Fishpool, G.
Abstract A density scan is performed in SOLPS5.0 for two divertor configurations of MAST Upgrade: (i) a short divertor silimiar to configurations in present‐day tokamaks, (ii) the Super‐X divertor. In the simulation, a clear roll‐over of the ion flux and plasma density at the target is observed as the plasma detaches. The separatrix density at which the transition occurs is estimated. In addition, we investigate the ability of the long‐legged divertor to reduce the target power loads and enhance the radiated power at higher collisionalities. We also study how distribution of power losses in the divertor region changes with the modification of geometry and we separately analyze neutral radiation and carbon ion line radiation. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)